AERODYNAMIC ANALYSIS OF ALOUETTE III ROTARY WINGS - Corpodean, Mircea (Research and science today, 2020)
EVER SINCE THE FIRST MODELS APPEARED, THE HELICOPTER HAS REPRESENTED AND WILL BE A SOLID SUBJECT OF STUDY, ALWAYS BEING A PLACE OF IMPROVEMENT IN ITS TECHNOLOGY WITH THE EVOLUTION OF SCIENCE. IN THIS PAPER I WILL PRESENT SOME IDEAS REGARDING THE AERODYNAMIC PERFORMANCES OF THE BEARING ROTORS, USING NUMERICAL SOFTWARE SIMULATIONS BASED ON A SCALE MODEL OF THE SA 316B HELICOPTER.